Wellens' syndrome: significance of ECG pattern recognition in the emergency department. Issue 10 (22nd September 2009) - Lilaonitkul, M; Robinson, K; Roberts, M
Abstract : Wellens' syndrome describes a characteristic pattern of ECG T-wave changes in association with critical narrowing of the left anterior descending coronary artery. Failure to diagnose this condition, with subsequent inappropriate management, may have fatal consequences. A case of Wellens' syndrome is reported in a young man presenting with "atypical chest pain" and the significance of its prompt recognition is discussed.